2020
DOI: 10.3390/diagnostics10060356
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG-PET Imaging Patterns in Autoimmune Encephalitis: Impact of Image Analysis on the Results

Abstract: Brain positron emission tomography imaging with 18Fluorine-fluorodeoxyglucose (FDG-PET) has demonstrated utility in suspected autoimmune encephalitis. Visual and/or assisted image reading is not well established to evaluate hypometabolism/hypermetabolism. We retrospectively evaluated patients with autoimmune encephalitis between 2003 and 2018. Patients underwent EEG, brain magnetic resonance imaging (MRI), cerebrospinal fluid (CSF) sampling and autoantibodies testing. Individual FDG-PET images were evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 31 publications
8
57
1
7
Order By: Relevance
“…Brain fludeoxy-glucose-positron-emission-tomography (FDG-PET) in patients with autoimmune encephalitis can show focal or diffuse areas of hypo- or hyper-metabolic activity. 69 In anti-NMDAR encephalitis, medial occipital hypometabolism is recognized. 70 In patients who do not respond to immunotherapy, or if the diagnosis remains unclear, brain biopsy may be considered, and the presence of inflammatory infiltrates may support the diagnosis of autoimmune encephalitis, but is not diagnostic.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…Brain fludeoxy-glucose-positron-emission-tomography (FDG-PET) in patients with autoimmune encephalitis can show focal or diffuse areas of hypo- or hyper-metabolic activity. 69 In anti-NMDAR encephalitis, medial occipital hypometabolism is recognized. 70 In patients who do not respond to immunotherapy, or if the diagnosis remains unclear, brain biopsy may be considered, and the presence of inflammatory infiltrates may support the diagnosis of autoimmune encephalitis, but is not diagnostic.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…Although not confirmed by our data, an EEG often provides important ways to suspect AE ( 8 ); however, EEG interpretation strongly depends on the rater's experience to identify characteristics of AE, such as a delta brush pattern in anti-NMDAR AB encephalitis ( 18 ).…”
Section: Discussionmentioning
confidence: 59%
“…Nevertheless, we observed a significant proportion of patients with pleocytosis and/or OCB in CSF in our study, which may be indicative of AE even in older patients with different subtypes of AE. Although other studies recommend CSF analysis only to rule out infections ( 8 , 26 ), our data suggest performing AB tests if the CSF cell count is increased or OCB are detected exclusively in CSF.…”
Section: Discussionmentioning
confidence: 62%
“…Recent studies [39,46] have shown a signi cant diagnostic contribution of semi-quanti cation in comparison to visual analysis alone in this context, leading to more comparable and accurate results. For example, Lv et al identi ed striatal hypermetabolism upon semi-quantitative analysis in 73% of patients who did not present with a visual metabolic striatal abnormality.…”
Section: Discussionmentioning
confidence: 99%
“…Above all, the methodology used for brain PET analysis in this issue is highly heterogeneous and hampered by several considerations: reduced spatial resolution of brain data extracted from whole-body 18 F-FDG PET/CT [34,35], lack of reproducibility of visual interpretation, and absence of standards for semi-quantitative analyses [36][37][38]; methods for intensity normalization are especially variable. Whereas some authors performed a standardization on global cerebral activity (i.e., proportional scaling) [32,34,35], others normalized to a supposedly preserved region of interest, which is always di cult to select in cases of encephalic impairment (for example the pons) [39]; nally, the method used is not speci ed in some studies [33,40]. In this context, larger cohort studies of patients suspected of DE are required, along with the standardization of 18 F-FDG PET/CT interpretation based on reproducible and e cient biomarkers to clarify the potential role of 18 F-FDG PET/CT in the diagnosis of DE [16].…”
Section: Introductionmentioning
confidence: 99%